Bimbingan Karir bagi Penerima Manfaat di Rumah Pelayanan Sosial PMKS “Pamardi Raharjo” Banjarnegara - Khuriatun Afifah; Lulu Saffanah; Novi Aryanti; Kholil Lur Rochman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
According to Sigmund Freud's psychoanalytic theory, mental disorders occur due to conflicts between the id, ego, and superego that give rise to anxiety and abnormal behavior. At the Pamardi Raharjo Banjarnegara Social Service House, this conflict is diverted through a skills guidance program that aims to improve the independence and quality of life of Beneficiaries (PM). The program includes training in doormat crafts, salted egg making, paving blocks, and flannel crafts, each of which is guided by a dedicated mentor and followed by a stabilized PM. The activity of making mats aims to train motor skills and social interaction and produce products with selling value. The making of salted eggs not only teaches production skills, but also fosters confidence and economic independence. Paving block activities are more focused on motor training and cooperation between PMs even though they are not yet worth selling. Meanwhile, flannel handicrafts guided by Mbak Retno became a new activity that provided space for expression and creativity. All of these activities are designed to distract PM's passive behavior and equip them with useful practical skills after leaving the orphanage. Thus, skills-based approaches have proven to be effective in supporting the overall rehabilitation and empowerment process of PM.